Identifying Starbucks Consumer Preferences and Satisfaction amid the Boycott Movement on Starbucks - arissal, Laden; Ismail, Ahmad; Munsi, Hardiyanti (Faculty of social and Political sciences, Hasanuddin University, 2024)
Starbucks a global coffee company and a giant in the coffee industry, has faced significant challenges impacting its business and trade activities worldwide due to being a target of boycott movements arising from the Israel-Palestine conflict. These boycotts, highly prevalent on social media, have led to a decline in Starbucks' profits globally, particularly in Indonesia. Despite the widespread boycott movements, some consumers continue to patronize Starbucks and choose it as their coffee destination. This study aims to explore how consumers perceive the Starbucks brand and identify the factors influencing their decision to continue choosing Starbucks amid the boycotts. The research employs a mixed-methods research (MMR) approach, combining qualitative and quantitative methods, utilizing surveys, observations, in-depth interviews, and secondary data analysis such as documents and supporting information. The selection of respondents and informants was conducted purposefully based on specific criteria. The findings reveal that Starbucks Dprima's consumers are predominantly individuals seeking a comfortable space to complete academic or professional tasks. The factors driving their continued patronage include the comfort and satisfaction they experience, along with the appealing facilities and services provided by Starbucks. The consumers' views on the boycott are generally neutral or opposed, as they believe clearer and more comprehensive information is necessary before accepting boycott-related claims. Additionally, personal consumer perspectives on the boycott issue play a key role in their decision to continue visiting and choosing Starbucks Dprima.